The Role of Self Confidence, Learning Strategies, and Teacher Support in Enhancing Student’s English Speaking Proficiency: Case Study in SMAS Kristen 1 Amahai - Aponno, Sience (International Journal of Business, Law, and Education, 2025)
This study investigates the role of self-confidence, learning strategies, and teacher support in enhancing students’ English speaking proficiency. Recognizing that speaking proficiency is a key component of communicative competence, the research explores how psychological, strategic, and pedagogical factors interact to improve students’ oral communication skills. A quantitative research design was employed, involving a sample of students from senior high schools. Data were collected through validated questionnaires and analyzed using SPSS, with multiple regression analysis applied to determine the contribution of each variable. The results revealed that self-confidence, learning strategies, and teacher support each had a positive and significant effect on students’ speaking proficiency, both individually and simultaneously. Self-confidence emerged as a strong predictor, enabling students to overcome anxiety and engage actively in speaking activities. Effective learning strategies were found to enhance skill acquisition and language use, while teacher support provided essential guidance, feedback, and motivation. These findings underscore the need for a holistic approach to language teaching that integrates psychological readiness, strategic learning, and supportive pedagogy. The study offers practical implications for educators, suggesting that fostering self-confidence, teaching effective learning strategies, and maintaining consistent teacher support can collectively lead to substantial improvements in students’ English speaking proficiency.